MEMECAHKAN CAPTCHA-TEXT TERDISTORSI DENGAN CONVOLUTIONAL NEURAL NETWORK - Muhammad Akbar Yasin (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
At the early stage of the development, CAPTCHA-text used distorted which difficult to solve by OCR technology. The development of AI technology, machine learning and image processing year after year makes the task to distinguish between human interaction and